2016
DOI: 10.1038/emi.2016.119
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of a Talaromyces marneffei active phospholipase B expressed in a Pichia pastoris expression system

Abstract: Phospholipase B is a virulence factor for several clinically important pathogenic fungi, including Candida albicans, Cryptococcus neoformans and Aspergillus fumigatus, but its role in the thermally dimorphic fungus Talaromyces marneffei remains unclear. Here, we provide the first report of the expression of a novel phospholipase gene, designated TmPlb1, from T. marneffei in the eukaryotic expression system of Pichia pastoris GS115. Sensitive real-time quantitative reverse-transcription PCR (qRT-PCR) demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
3
10
2
Order By: Relevance
“…A previous investigation of MRSA from inpatients in China found that 28.6% of isolates were pvl –positive 7. Several other recent studies also showed that about 10% of MRSA isolates were pvl -positive 2,48. Our results showed that only 3.0% of MRSA isolates were pvl -positive, which is very different from these other studies 2,48.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A previous investigation of MRSA from inpatients in China found that 28.6% of isolates were pvl –positive 7. Several other recent studies also showed that about 10% of MRSA isolates were pvl -positive 2,48. Our results showed that only 3.0% of MRSA isolates were pvl -positive, which is very different from these other studies 2,48.…”
Section: Discussioncontrasting
confidence: 99%
“…Several other recent studies also showed that about 10% of MRSA isolates were pvl -positive 2,48. Our results showed that only 3.0% of MRSA isolates were pvl -positive, which is very different from these other studies 2,48. However, 34.4% of our MSSA isolates harbored the pvl gene, similar to the prevalences reported by recent studies in Chongqing 38…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies suggested that DNA priming immunization induces higher levels of antigen-specific B-cell responses. 25,26 Consistently, the Cells/DNA method resulted in the highest number of antigenspecific scFv clones in this study (Figure 4a), although functional experiments will be necessary to determine if these scFv clones translate to better mAbs.…”
Section: Discussionsupporting
confidence: 65%
“…He et al 2016 performed expression and characterization of Talaromyces marneffei active phospholipase B using Pichia pastoris GS115 expression system. Using Ni-affinity chromatography, the protein concentration of active TmPLB1 was 240.4 mg L −1 of the culture medium [43]. It usually takes 5-7 days for expression of recombinant protein in Pichia pastoris expression system.…”
Section: Recombinant Tmplb1 Expression and P Simple Point Charge (Spcmentioning
confidence: 99%